A SURVEY ON THE COMMUNITY SATISFACTION INDEX BASED ON KEPMENPAN NO. 25/M.PAN/2/2004 AT KANUJOSO DJATIWIBOWO REGIONAL GENERAL HOSPITAL, BALIKPAPAN IN 2018 - Savitri, Mieke; Armando, Dea Yasmine (UI Scholars Hub, 2019)
Community Satisfaction Index (CSI) Survey is used to measure the community’s perception on the services that they receive. In hospitals, it is used to determine whether a service or facility needs to be improved or not, and where it must be improved. In 2018, a descriptive qualitative study was performed at RSUD Dr. Kanujoso which would measure the public’s perception on the services that the hospital provided. The survey was based on the 14 aspects of CSI of the State Apparatus Empowerment Minister Decree No. 25/M.PAN/2/2004. We discovered that the highest rate was held by the Hemodialysis Unit with 100% and the lowest was held by the Medical Rehabilitation Unit with 74.18%. The other units ranged between 74.89%-90.83%. While the average score for the hospital was 78.42%, which meant that the hospital’s perfoemance was good. In general, the hospital provided good service, as evident in the average score of 78.42%. 93.6% of patients prefer to return to the hospital and 97,6% would recommend the hospital. Although some improvements were necessary, such as in the speed and fairness. Therefore, the staff involved in those areas should received further training.